Pengaruh Kecukupan Modal, Non Performing Loan (NPL) dan Dana Pihak Ketiga Terhadap Profitabilitas Perbankan (Studi Kasus Pada Bank Umum Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2018) - Krensia Isidora Wea; I Ketut Darma; Kompiang Bagiada (Warmadewa Economic Development Journal (WEDJ), 2022)
This study is entitled "Effect of Capital Adequacy, Non-Performing Loans (NPLs), and Third-Party Funds on Banking Profitability (on Commercial Banks Listed on the Indonesia Stock Exchange). The purpose of this is to determine the effect of Capital Adequacy, Non-Performing Loans, and Third Party Funds on Profitability. The number of samples in this study was 10 companies. The type of data in this study is secondary data with data collection methods in the form of documentation. The analysis technique used is the multiple linear analysis techniques were previously tested research instruments and classical assumption tests. The results showed that the Capital Adequacy (X1) variable had a positive and significant effect on profitability (Y), the Non-Performing Loan variable (X2) had a negative and significant effect on profitability (Y), and the Third Party Fund variable (X3) had a positive and significant effect on profitability (Y).